A case report of metastatic renal oncocytoma. (November 2017) - Amante, Gionathan; Mei Goh, Yan; Andrews, Henry
Abstract : Introduction: Renal oncocytomas are renal tumours that are largely considered to be benign. They represent 5.5% of all renal tumours and the age-standardised incidence is 0.3 per 100, 000/year in men and women. 1 Despite this, there have been reported cases where these tumours have developed metastases. We report the case of a patient who had a right radical nephrectomy for renal oncocytoma who then presents nine years later with a pathological neck of femur (NOF) fracture secondary to metastases, suggesting malignant behaviour of the tumour. Case description: A 62-year-old lady presented in December 2010 with shortness of breath on exertion, frontal headache and malignant hypertension. She was treated with Ramipril and her blood pressure subsided. On discharge she underwent further investigations, including 24hour urine catecholamine test – (normal), and abdominal ultrasound which revealed a mass in the right kidney. Computerized tomography (CT) confirmed a well-defined lower pole right renal solid mass measuring 7.5x5.7cm, extending to the renal pelvis with compression of the vascular pedicle. There was no evidence of extrarenal extension. Renal cell carcinoma stage T2 was suggested. She underwent a right laparoscopic nephrectomy and recovered well from the operation. Histology confirmed oncocytoma with atypical features of extrarenal invasion, absence of Hale's colloidal blue staining, negativity for cytokeratin 7 and positive vimentin staining. This patient had yearly follow-up CT. Four years after her first surgery, a nodule was noted in the right nephrectomy bed. Surgical excision confirmed recurrent oncocytoma. Two years after this she presented with pathological fracture of her right neck of femur. A bone biopsy confirmed metastatic disease. She had a dynamic hip screw fixation. Results and Conclusions: The World Health Organization classifies renal oncocytoma as benign neoplasm. 2 Nevertheless there are case reports of metastatic disease in these tumours. Studies have revealed a classical pattern with typical features of benign neoplasia in 57.5-67% of cases. Malignant features such as atypical histological pattern, focal necrosis, multinucleation, mitotic activity, degenerative atypia and invasion of extrarenal fat have been described in others. Despite this, not all patients with such features progress to developing metastatic disease at 5-year follow-up. In fact only 2 patients out of 42 with atypical features developed metastatic disease. 3 This suggests that there is a potential for metastatic transformation of this tumour, especially in the group with features of atypia. There is a however, paucity of information in published literature regarding this. The risk stratification of these atypical features will be a good start. Clearly, further research by way of genetic assessment, including chromosomal and tumour markers is required, as part of future diagnosis and management algorithm. Take home message: Metastatic renal oncocytomas are extremely rare. Little is known about the atypical features that predispose metastatic transformation. Our patient developed local recurrence and a distant metastatic lesion with fracture neck of femur 6 years later. Our extensive search of literature has shown only 2 other reported cases of metastatic oncocytomas in the bone being the tibia and femur. The patient with the femoral fracture had multiple bone metastatic lesions. Further research into the biological features and characteristics of this extremely rare condition is required. This may help stratifying patients into metastatic risk potentials. Perhaps treatment plans can be tailored accordingly.